Kajian Teknis dan Ekonomis Peledakan di Pit 1 PT. Pebana Adi Sarana Kabupaten Lima Puluh Kota Sumatera Barat - Fadhlan Assany; Raimon Kopa (Journals Mining Engineering : Bina Tambang, 2021)
Abstract. PT. Pebana Adi Sarana is located in Jorong Mudik Pasar Manggilang, Pangkalan Koto Baru District, Lima Puluh Kota Regency, West Sumatra Province with an area of 54.74 Ha and has an estimated reserves of andesite stones of 3.925.900 Tons. During the study, the results of blasting were 30% -40% while the desired target was 15% -20%. The purpose of this study is to improve the blasting results in the field by comparing the actual blasting results with the proposed blasting and economic studies by making a comparison of the proposed results against the costs incurred in blasting activities and the use of a breaker. The blasting geometry recommendation of the research method is based on the theory of R. L. Ash and C. J. Konya. The results of the study using actual geometry data showed that the fragmentation results of the Split desktop were 33% and the cost of blasting per tonnage was IDR 6,891/ton. Meanwhile, based on the proposed geometry design with the theory of R. L. Ash and the theory of C. J. Konya, the fragmentation results using Split desktop were 19.37% and the cost of blasting per tonnes was IDR 5,294/Ton. The difference between the cost of the actual geometry and the test geometry is IDR 1.596/TonKeywords : Blasting Geometry, Blasting Fragmentation, Theory of R. L.Ash and C. J. Konya and Blasting Costs